The Synergy of AI and Non-AI Tools in Higher Education Self-Directed ESL/EFL: A Systematic Literature Review - Leow, Min Hui; Hassan, Norhaslinda binti; Marzaini, Anwar Farhan bin Mohamad; Susilawati, Lusi; Hestiana, Siska; Sya’ban, Muhammad Satria (Journal of Teaching and Learning, 2026)
There is a scarcity of studies that delve into the potential synergy between AI and non-AI tools. This review examines the integration of AI and non-AI tools in supporting self-directed ESL/EFL. Searches were conducted using Scopus, Web of Science (WoS), and EBSCO, covering publications from 2020 to the first quarter of 2025. A total of 178 peer-reviewed empirical studies were included, selected in accordance with PRISMA 2020 guidelines. The findings reveal a growing trend in AI adoption, with AI-powered chatbots, language learning platforms, automatic speech recognition (ASR), automated writing evaluation (AWE), and translation tools being the most prevalent. Non-AI tools such as game-based platforms, language massive open online courses, social media, learning management systems, virtual reality, and web-based lexicographic tools also demonstrated strong support for self-directed learning. Effectiveness ratings showed both AI and non-AI tools were consistently perceived as neutral to positive. The study highlights the potential synergy between AI and non-AI tools, in which their complementary strengths address each other's limitations. This review contributes to pedagogical innovation by identifying emerging technologies and proposing integrated strategies to enhance self-directed ESL/EFL learning. It offers actionable insights for educators, curriculum designers, and researchers aiming to foster equitable, sustainable, and tech-enhanced language education.